Optimizing the Entrepreneurs' Crowdfunding in Sport Business - Mahdieh Hossein Aliani; Nematullah Nemati; Tahereh Bagherpour (Sports Business Journal)
Purpose: This research aims to identify and validate Iranian sports entrepreneurs' optimal use of crowdfunding.Methodology: The research method is mixed. In the qualitative section, the participants included 16 sports management professors, entrepreneurship management, sports entrepreneurs, and sports business people in the interview, and the data were analyzed by Maxqda version—2020 software. Furthermore, 360 participants participated in the survey during the quantitative section, and the data was analyzed with Smart PLS software.Findings: The findings showed casual elements, including entrepreneurial attitude, human capital, and policies. The background conditions include the institutionalization of entrepreneurship, business management transparency and improvement, a customer-oriented culture, and cultural and social factors. Also, the intervening factors comprised laws and regulations, financial and economic elements, protective laws, and information technology factors. The practical strategies also included expert forces, trust building, creating supportive and monetary policies, and communicating with entrepreneurs. Finally, the results showed the growth of sports businesses, distribution of justice in financial resources, economic productivity, and positive attitude toward sports entrepreneurs as social capital. According to the results, the identified factors can provide the necessary ground for collective financing by sports business entrepreneurs.Originality: Funding has always been one of the main challenges of entrepreneurs, and crowdfunding can be an effective way to provide the capital a start-up company needs. The purpose of this study is to optimize collective capital by sports entrepreneurs by a quantitative study.